Resident-performed laser peripheral iridotomy in primary angle closure, primary angle closure suspects, and primary angle closure glaucoma - Kam JP; Zepeda EM; Ding L; Wen JC (Clinical Ophthalmology, 2017)
Jason P Kam, Emily M Zepeda, Leona Ding, Joanne C Wen Department of Ophthalmology, University of Washington, Seattle, WA, USA Purpose: To investigate the power use and complication frequency of resident-performed laser peripheral iridotomy (LPI).Methods: A retrospective analysis of 196 eyes from 103 patients who underwent neodymium: yttrium-aluminum-garnet laser iridotomy performed by resident physicians from January 1, 2010 through April 30, 2015 at a university-based county hospital was done. All patients were treated for primary angle closure, primary angle closure suspects, and primary angle closure glaucoma. Data were collected on pre- and post-laser intraocular pressure (IOP), ethnicity, laser parameters and complications. Mean power use and frequency of complications were evaluated. Complications included elevated post-laser IOP at 30–45 minutes (≥8 mmHg), hyphema, aborted procedures, and lasering non-iris structures. The number of repeated LPI procedures, was also recorded.Results: Mean total power used for all residents was 78.2±68.7 mJ per eye. Power use by first-year trainees was significantly higher than second- and third-year trainees (103.5±75.5 mJ versus 73.7±73.8 mJ and 67.2±56.4 mJ, respectively, p=0.011). Complications included hyphema or microhyphema in 17.9% (35/196), IOP spikes in 5.1% (10/196), aborted procedures in 1.1% (3/196) and lasering non-iris structures in 0.5% (1/196). LPI was repeated in 22.4% of cases (44/196) with higher incidence of repeat LPI among non-Caucasian compared to the Caucasian subjects (p=0.02). Complication rates did not differ with increased training (p=0.16).Conclusion: Total power used for LPI decreased with increased resident training, while the complication rate did not differ significantly among resident classes. Complication rates were comparable to rates reported in the literature for attending-performed LPIs. Keywords: laser, iridotomy, resident, complications, power, energy